A 15-Gene Signature and Prognostic Nomogram for Predicting Overall Survival in Non-Distant Metastatic Oral Tongue Squamous Cell Carcinoma - Liu, Muyuan; Tong, Litian; Liang, Bin; Song, Xuhong; Xie, Lingzhu; Peng, Hanwei; Huang, Dongyang (Frontiers in Oncology, 2021)
Background: Oral tongue squamous cell carcinoma (OTSCC) is a devastating tumor with poor prognosis. There is an urgent need for reliable biomarkers to help predict prognosis and guide treatment for OTSCC. In the current study, we aimed to develop a robust multi-gene signature and prognostic nomogram to predict the prognosis of patients with OTSCC. Methods: OTSCC-related differentially-expressed genes were screened from The Cancer Genome Atlas (TCGA) database. Univariate Cox regression based on 1000 bootstrap replicates, LASSO regression and stepwise multivariate Cox regression were utilized to develop a novel multi-mRNA signature for predicting overall survival in OTSCC. The concordance index, area under receiver operating characteristic (ROC AUC) and calibration curve were employed to assess the prediction capacity of the novel multi-gene model. In addition, a prognostic nomogram was constructed to facilitate the clinical use of the fitted model. The Kaplan-Meier with log-rank test was employed to assess differences in overall survival. Results: We successfully established a novel 15-mRNA prognostic model for predicting overall survival of OTSCC, involving ADTRP, ITGA3, RFC4, CCDC96, CYP2J2, NELL2, SPHK1, SPAG16, HBEGF, S100A9, EGFL6, ADGRG6, PDE4D, ABCA4 and CTTN. The prediction ability of this 15-gene signature was independent of other clinicopathological factors, with an HR of 11.5 (95% CI: 4.70–28.3). Moreover, bootstrap analysis yielded a C-index of 0.849, with a 3-year AUC of 0.907 and 5-year AUC of 0.944, which implied excellent prediction accuracy of the fitted model. In addition, a prognostic nomogram integrating risk group, grade, T stage and N stage was established. Conclusion: Our results demonstrate our 15-gene signature could predict overall survival in oral tongue squamous cell carcinoma efficiently and precisely. Moreover, the prognostic nomogram integrating the 15-gene signature and clinicopathological factors should be valuable for clinical treatment decision-making and patient counseling.